<< Chapter < Page Chapter >> Page >

Eliminating the parameter

In many cases, we may have a pair of parametric equations but find that it is simpler to draw a curve if the equation involves only two variables, such as x and y . Eliminating the parameter is a method that may make graphing some curves easier. However, if we are concerned with the mapping of the equation according to time, then it will be necessary to indicate the orientation of the curve as well. There are various methods for eliminating the parameter t from a set of parametric equations; not every method works for every type of equation. Here we will review the methods for the most common types of equations.

Eliminating the parameter from polynomial, exponential, and logarithmic equations

For polynomial, exponential, or logarithmic equations expressed as two parametric equations, we choose the equation that is most easily manipulated and solve for t . We substitute the resulting expression for t into the second equation. This gives one equation in x and y .

Eliminating the parameter in polynomials

Given x ( t ) = t 2 + 1 and y ( t ) = 2 + t , eliminate the parameter, and write the parametric equations as a Cartesian equation.

We will begin with the equation for y because the linear equation is easier to solve for t .

y = 2 + t y 2 = t

Next, substitute y 2 for t in x ( t ) .

x = t 2 + 1 x = ( y 2 ) 2 + 1 Substitute the expression for  t  into  x . x = y 2 4 y + 4 + 1 x = y 2 4 y + 5 x = y 2 4 y + 5

The Cartesian form is x = y 2 4 y + 5.

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Given the equations below, eliminate the parameter and write as a rectangular equation for y as a function
of x .

x ( t ) = 2 t 2 + 6 y ( t ) = 5 t

y = 5 1 2 x 3

Got questions? Get instant answers now!

Eliminating the parameter in exponential equations

Eliminate the parameter and write as a Cartesian equation: x ( t ) = e t and y ( t ) = 3 e t , t > 0.

Isolate e t .

x = e t e t = 1 x

Substitute the expression into y ( t ) .

y = 3 e t y = 3 ( 1 x ) y = 3 x

The Cartesian form is y = 3 x .

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Eliminating the parameter in logarithmic equations

Eliminate the parameter and write as a Cartesian equation: x ( t ) = t + 2 and y ( t ) = log ( t ) .

Solve the first equation for t .

            x = t + 2      x 2 = t ( x 2 ) 2 = t Square both sides .

Then, substitute the expression for t into the y equation.

y = log ( t ) y = log ( x 2 ) 2

The Cartesian form is y = log ( x 2 ) 2 .

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Eliminate the parameter and write as a rectangular equation .

x ( t ) = t 2 y ( t ) = ln t t > 0

y = ln x

Got questions? Get instant answers now!

Eliminating the parameter from trigonometric equations

Eliminating the parameter from trigonometric equations is a straightforward substitution. We can use a few of the familiar trigonometric identities and the Pythagorean Theorem.

First, we use the identities:

x ( t ) = a cos t y ( t ) = b sin t

Solving for cos t and sin t , we have

x a = cos t y b = sin t

Then, use the Pythagorean Theorem:

cos 2 t + sin 2 t = 1

Substituting gives

cos 2 t + sin 2 t = ( x a ) 2 + ( y b ) 2 = 1

Eliminating the parameter from a pair of trigonometric parametric equations

Eliminate the parameter from the given pair of trigonometric equations where 0 t 2 π and sketch the graph.

x ( t ) = 4 cos t y ( t ) = 3 sin t

Solving for cos t and sin t , we have

x = 4 cos t x 4 = cos t y = 3 sin t y 3 = sin t

Next, use the Pythagorean identity and make the substitutions.

cos 2 t + sin 2 t = 1 ( x 4 ) 2 + ( y 3 ) 2 = 1 x 2 16 + y 2 9 = 1

The graph for the equation is shown in [link] .

Graph of given ellipse centered at (0,0).
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Questions & Answers

The sequence is {1,-1,1-1.....} has
amit Reply
circular region of radious
Kainat Reply
how can we solve this problem
Joel Reply
Sin(A+B) = sinBcosA+cosBsinA
Eseka Reply
Prove it
Eseka
Please prove it
Eseka
hi
Joel
June needs 45 gallons of punch. 2 different coolers. Bigger cooler is 5 times as large as smaller cooler. How many gallons in each cooler?
Arleathia Reply
find the sum of 28th term of the AP 3+10+17+---------
Prince Reply
I think you should say "28 terms" instead of "28th term"
Vedant
if sequence sn is a such that sn>0 for all n and lim sn=0than prove that lim (s1 s2............ sn) ke hole power n =n
SANDESH Reply
write down the polynomial function with root 1/3,2,-3 with solution
Gift Reply
if A and B are subspaces of V prove that (A+B)/B=A/(A-B)
Pream Reply
write down the value of each of the following in surd form a)cos(-65°) b)sin(-180°)c)tan(225°)d)tan(135°)
Oroke Reply
Prove that (sinA/1-cosA - 1-cosA/sinA) (cosA/1-sinA - 1-sinA/cosA) = 4
kiruba Reply
what is the answer to dividing negative index
Morosi Reply
In a triangle ABC prove that. (b+c)cosA+(c+a)cosB+(a+b)cisC=a+b+c.
Shivam Reply
give me the waec 2019 questions
Aaron Reply
the polar co-ordinate of the point (-1, -1)
Sumit Reply
Practice Key Terms 1

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask